Polymorphisms of rDNA genes in Cyberlindnera yeast suggest birth-and-death evolution events - Bizarria, Rodolfo [UNESP]; Pietrobon, Tatiane De Castro [UNESP]; Ferreira, Henrique [UNESP]; Rodrigues, Andre [UNESP] (Oxford University Press (OUP), 2023)
In eukaryotes, the ribosome machinery is encoded by repeats of the ribosomal RNA genes: 26/28S, 18S, 5.8S, and 5S, structured in tandem arrays and frequently homogenized within a genome. This homogenization is thought to be driven by concerted evolution, evolving as a unit, which contributes to its target as the species barcode in modern taxonomy. However, high heterogeneity of rDNA genes has been reported, including in Saccharomycotina yeasts. Here, we describe the polymorphisms and heterogeneity of D1/D2 domains (26S rRNA) and the intergenic transcribed spacer of a new yeast species with affinities to the genus Cyberlindnera and their evolution. Both regions are not homogenized, failing the prediction of concerted evolution. Phylogenetic network analysis of cloned sequences revealed that Cyberlindnera sp. rDNAs are diverse and evolved by reticulation rather than by bifurcating tree evolution model. Predicted rRNA secondary structures also confirmed structural differences, except for some conserved hairpin loops. We hypothesize that some rDNA is inactive within this species and evolves by birth-and-death rather than concerted evolution. Our findings propel further investigation into the evolution of rDNA genes in yeasts.
Keywords: birth-and-death evolution; concerted evolution; Cyberlindnera; rDNA polymorphisms; reticulation; rRNA secondary structures